Ukraińskie leksykultury kulinarne w dydaktyce ukrainistycznej - Budziak, Anna (Studia Ukrainica Posnaniensia, 2025)
The article is devoted to the problem of the joint development of linguistic and cultural competence in the process of teaching Ukrainian as a foreign language. The analysis uses the concept of developing cultural competence in the methodology of teaching a foreign language developed by the French researcher Robert Galisson and the term lexiculture he introduced. The reflections focus on selected names of dishes and food products that are exponents of Ukrainian cultural identity (борщ, вареник, гречка, сало, гарбуз, кавун, паляниця, перець). The additional semantic content of these names, not listed in dictionaries, is indicated and the specificity of the functioning of such lexemes in Ukrainian compared to Polish is described, drawing attention to the great discrepancies in this area.